STRATEGI PEMERINTAH DAERAH KABUPATEN BANYUMAS DALAM MENCEGAH KORUPSI ANGGARAN PENDAPATAN DAN BELANJA DAERAH (APBD) DI KABUPATEN BANYUMAS - Tri Ayu Suciana; Esti Ningrum; Haris Kusumawardana; Agoes Djatmiko (Cakrawala Hukum: Majalah Ilmiah Fakultas Hukum Universitas Wijayakusuma, 2024)
Abstrak . Banyumas Regency is one of the regencies that received the highest ranking for corruption prevention. According to the Corruption Eradication Commission's Monitoring Center for Prevention (MCP) corruption prevention instrument, Banyumas Regency is ranked sixth at the national level with an index of 95.79. This research was conducted to find out the strategies of the Banyumas Regency Regional Government in preventing corruption of the Regional Budget (APBD) in Banyumas Regency and the obstacles of the Banyumas Regency Regional Government in implementing strategies to prevent corruption of the Regional Budget (APBD) in Banyumas Regency. The research method used is normative juridical using secondary data sources and primary data sources in the form of data from interviews with the Banyumas Regency local government consisting of the Regional Secretariat of the Legal Section and the Banyumas Regency Regional Inspectorate. Based on the results of the study, that the strategies and effective efforts of the Banyumas Regency local government in preventing corruption of the Regional Budget (APBD) in Banyumas Regency can be done through the establishment of regulations, handling conflicts of interest, fostering the State Civil Apparatus (ASN), using the Monitoring Center for Prevention (MCP), using the Whistleblowing System (WBS), using complaint stalls, conducting investigative audits, implementing the Government Internal Control System (SPIP), and carry out the duties and functions of local government on the regional revenue and expenditure budget (APBD). The obstacles of The Banyumas Regency Regional Government in preventing Corruption in the Regional Budget (APBD) in Banyumas Regency include delays in the implementation of activity schedules, the effectiveness of regulations, and the incompatibility of public complaints. Keyword: Corruption, APBD, Banyumas Regency.